O45: DEFINING CELL-ENRICHED MICRORNAS TO SUPPORT RATIONAL BIOMARKER SELECTION IN HUMAN RENAL TRANSPLANTATION. (27th April 2021) - Connor, K; Teenan, O; Thomas, R; Banwell, V; Finnie, S; Monaghan, ML; Cairns, C; Tannahill, G; Harrison, E; Conway, B; Marson, L; Denby, L; et al.
Abstract: Introduction: MicroRNAs are promising biomarkers of renal disease, however the cellular origin of their expression is usually unclear limiting their interpretation when measured in renal biopsies and urine. We hypothesised that by first defining renal cell-enriched microRNAs, we could select biomarkers based on the expected histopathological profile. Method: Small RNA-sequencing of cortical, proximal tubular (LTL), macrophage (F480), endothelial (CD31) and fibroblast (PDGFRb) populations from the reversible unilateral ureteric obstruction (rUUO) murine model was performed. Hierarchical clustering was used to identify clusters. Findings were translated into an ischaemia reperfusion injury (IRI) model and then into urine samples from renal transplant recipients (n=16) with delayed graft function (DGF) vs. those with primary function. Result: Kidney injury resulted in significant macrophage infiltration and tubular injury which improved upon reversal. We characterised novel microRNA clusters enriched for each cell type. With injury there was a significant increase in macrophage (p<0.0001), fibroblast (p<0.01) and decrease in proximal tubule (p<0.0001) enriched microRNAs vs. non-enriched microRNAs. We validated macrophage enriched miR-18a, miR-16 and tubular enriched miR-194 in the IRI model, demonstrating that microRNA expression reflected the histological profile. In humans, urinary miR-16 (FC 16.9; p<0.05) and miR-18a (FC 10: p=0.06) were upregulated at day 2 in patients with DGF; outperforming the traditional injury marker KIM1. Conclusion: This is the first study to characterise cell-enriched microRNAs during renal injury and repair. By defining the source of microRNA expression we were able to rationally select miR-16 and miR-18a as promising urinary biomarkers of renal injury. Take-home message: We have found that microRNAs have differences in expression between cell types and renal injury states which is important when considering microRNA expression in samples composed of varying cellular composition. By defining the cellular origins of microRNA expression we were able to rationally select microRNA biomarkers of human renal injury.